الشرط الاتفاقي بالالتزام بعدم المنافسة (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يصدر قانون العمل عادة تحقيقاً لمطالب اقتصادية واجتماعية ملحة من أهمها تحقيق استقرار العلاقات الاجتماعية والمساواة في المعاملة بين العاملين ورفع مستوى المعيشة لذلك تعرض قانون العمل لكثير من الشروط الموضوعية والشكلية التي ترافق إبرام عقد العمل وتنفيذه ولا شك أن هذا الأمر من إيجابيات قانون العمل لأنه بهذه الخطوة يحافظ على استقرار علاقات العمل الفردية ويضمن حسم ما قد ينشأ من خلافات بين العامل وصاحب العمل بشأنها مما ينعكس ايجابيا على السلم والأمن الاجتماعي إلا أننا لم نجد مبرراً منطقياً وقانونياً لعدم قيام المشرع في قانون العمل ببحث موضوع الشرط الاتفاقي بعدم المنافسة وترك الأمر للقانون المدني .وعليه فقد ارتأينا تسليط الضوء على هذا الموضوع .The Labor Code is usually issued to execute persistent economic and social demands. The most important ones are achieving the Stabilization of the social relationships, the Equal treatment among workers and raising the Living standards . As a result the Labor Code has been exposed to several objective and nominal conditions which accompany signing the contract and accomplishing it. Undoubtedly this is one of the positive points in the Labor Code. Due to the fact that it secures the stabilization of the individual work relationships and guarantees an end to the controversies that might arise between the worker and the employer . This will have a positive influence on the peace and social security . However we couldn’t find a reasonable and legal excuse for not having the Legislator of the labor code studying the conventional clause of not competing and leaving the subject for the Civil law. So we have decided to spot a light on this subject .